The pathogenesis, risk factors, diagnosis and treatment of Acanthamoeba keratitis - Mingliang Bao; Hai Bao; Shuqing Wang; Hongyan Zhou (Frontiers in Medicine)
Acanthamoeba keratitis (AK) is a rare corneal disease that can lead to permanent visual impairment. Its incidence is relatively low when compared with that of other forms of infectious keratitis. As early clinical diagnosis of AK is challenging (e.g., overlapping symptoms, lack of specific diagnostic tools, etc.), it is often misdiagnosed as other types of infectious keratitis, such as viral keratitis or fungal keratitis. Once a patient is diagnosed with AK, the prognosis is extremely poor unless an early start of an aggressive treatment program is implemented, as timely diagnosis and treatment are closely related to a good prognosis. AK can be diagnosed through corneal scraping, culture, polymerase chain reaction, or in vivo confocal microscopy. Drug treatment typically involves a combination of biguanide and diamine. In advanced stages of the disease, corneal transplantation is required. This review focuses on the pathogenesis, risk factors, early diagnosis, and treatment of Acanthamoeba keratitis. This review aims to enhance the understanding of Acanthamoeba keratitis.